Correlation between body mass index and serum anti-Mullerian hormone level in subfertile women at BIRDEM General Hospital, Dhaka - Tasnim, Maliha; Husain, Mahzabin; Sultana, Tasnia; Chowdhury, Jannatul Ferdous; Aziz, Effat; Sarmin, Rubab; Akter, Salma; Monir-Ul-Islam, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Anti-Mullerian hormone (AMH) is a crucial marker for ovarian reserve, reflecting ovarian function due to its secretion by antral follicles. Obesity can adversely affect fertility, potentially altering AMH production. The aim of this study was to assess the correlation between body mass index (BMI) and serum anti-Mullerian hormone (AMH) level in subfertile women. Methods: This cross-sectional analytical study was carried out in the department of obstetrics and gynecology, BIRDEM General Hospital, Dhaka, over a period of 18 months from January 2023 to June 2024. Results: Between BMI≥25 kg/m2 and <25 kg/m2 groups there were no significant differences in age distribution (mean ages: 30.5 versus 30.4 years, p=0.912). There were no significant differences in education, occupation, or income distribution between two groups. Menstrual regularity and flow differed significantly, with more irregular cycles and heavier flow in the BMI≥25 group (p<0.0001 and p=0.049, respectively). Serum AMH levels were significantly lower in the BMI≥25 group (1.7 versus 3.1, p<0.0001). A negative correlation was found between serum AMH levels and BMI, indicated that serum AMH level decreases with increasing BMI (p<0.0001). Age and BMI were inversely significantly associated with serum AMH level adjusted for each other. Conclusions: Higher BMI was associated with lower serum AMH levels in subfertile women, suggesting that elevated BMI may negatively impact serum AMH level which is a potential marker of ovarian reserve.